A novel bandpass waveguide filter structure on SIW technology - Sotoodeh, Z.; Biglarbegian, B.; Hojat Kashani, F.; Ameri Mahabadi, H. (2008)
Taking the advantage of common waveguide filters and SIW technology, a new filter structure is proposed.This structure can be implemented for various microwave frequencies by choosing appropriate low loss substrates.An example of suggested structure in Ku band is presented in this paper.The filter is designed and simulated on a low loss RT/Duroid 5880 laminate.The resulted filter has a Quality factor around 150.The main advantage of the structure is low size and cost, simplicity in fabrication, and the ability of integration with other elements of the circuit.